2000
DOI: 10.1023/a:1009060800999
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pramipexole, used as an adjunct to antidepressants or mood stabilizers, appeared to be effective and safe in the treatment of unipolar and bipolar depression. These uncontrolled, retrospective, naturalistic pilot data require confirmation by controlled research before conclusions can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…119, 120, 121, 122, 123, 124, 125, 126, 127 Although there have not been any RCTs investigating the efficacy of methylphenidate or amphetamines in bipolar depression, the available open-label and naturalistic studies point towards a benefit of stimulants in a selected group of patients with drowsiness and fatigue. 128, 129, 130, 131 Randomised controlled studies and open-label reports with other stimulant like agents such as modafinil and its R-enantiomer, armodafinil also indicate efficacy in bipolar depression although the development programme for armodafinil failed.…”
Section: Modulation Of the Dopamine System And Treatment Of Bipolar Dmentioning
confidence: 99%
“…119, 120, 121, 122, 123, 124, 125, 126, 127 Although there have not been any RCTs investigating the efficacy of methylphenidate or amphetamines in bipolar depression, the available open-label and naturalistic studies point towards a benefit of stimulants in a selected group of patients with drowsiness and fatigue. 128, 129, 130, 131 Randomised controlled studies and open-label reports with other stimulant like agents such as modafinil and its R-enantiomer, armodafinil also indicate efficacy in bipolar depression although the development programme for armodafinil failed.…”
Section: Modulation Of the Dopamine System And Treatment Of Bipolar Dmentioning
confidence: 99%
“…It was introduced for treating motor symptoms in patients with idiopathic Parkinson's disease (PD) [1] and has been shown to be effective by various clinical trials [2], [3]. In addition, various studies have recently found antidepressive effects of pramipexole not only in patients with PD complicated by depressive state [4], [5], [6], [7], but also in depressive patients without parkinsonian symptoms [8], [9], [10], [11], [12], [13], [14], [15], [16]. Its antidepressive effects have been also shown in animal experiments [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…25 , 26 Moreover, Pramipexole, a D3 preferring agonist, was found to be effective in both unipolar and bipolar depression. 27 …”
Section: Introductionmentioning
confidence: 99%